Measuring the dynamics of BRAC's contribution to employment generation - Halder, Shantana R. (Research and Evaluation Division, Brac, 2019)
This study explores the areas of employment /types of job created through BRAC activities and estimates the actual achievements of BRAC in terms of numbers and/ or person-years of employment generated. BRACpaid full-time and part-time employment and the non-paid selfemployment are considered in the analysis. The study has rwo parts. The first part gives a picture about the dynamics of BRAC's overall achievements in number of jobs created. The second part focused the changes that have occurred in the last five years in one specific RDP area. For both, the Head office MIS data and the case study results were used. Results show that in 1999 BRAC employed 40,756 full-time and 46,420 part-time workers. To carry out certain other work on temporary basis it employed a large number of individuals which created 1,463 person-years of employment. Annual growth rate for both full and part-time employment in the last five years was around 11%. Regarding self employment, in 1999 BRAC created 2.96 million jobs (either full-time or parttime), of them 2.85 millions are direct RDP beneficiaries. Annual growth rate of RDP beneficiaries was found to be 25.5%. Extension of programme activities to new geographical locations and inclusion of new activities are the major contributing factors explaining the high growth rate. In 1999 the total RDP beneficiaries generated 627,621 person-years of additional employment, i.e., 0.19 person-years per beneficiary. The case study results show that the MELA loan that has been introduced in Jhikargacha in 1999 created, on average, 0.56 person-years of additional employment per enterprise. A more detailed analysis of the employment dynamics based on field-based data representing various regions will be covered through the Third Impact Assessment Study.